MENUJU KEUNGGULAN MELALUI MALCOLM BALDRIGE DENGAN DAMPAK POSITIF DAN NEGATIFNYA UNTUK DUNIA BISNIS - Nita Novia Nugraha Putri; Intri Ayu Murti; Evi Zulfiah; Bekti Widanta; Kusuma Chandra Kirana (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to determine the positive and negative impacts of applying the Malcolm Baldrige Method in the business world. This study also aims to find out whether it is possible if the Malcolm Baldrige Method is applied to MSMEs in Indonesia which in their business development are distinguished by 4 criteria namely Livelihood Activities, Micro Enterprise, Small Dynamic Enterprise and Fast Moving Enterprise, while for the Baldrige Assessment there are 7 pillars of assessment namely Leadership, Strategic Planning, Customer Focused, Measurement-Analysis-Knowledge Management, Workforce Focused, Operations Focused, and Results. To achieve the objectives of this study, researchers used a qualitative critical journal approach and literacy studies. This research finds several positive and negative impact points from the application of the Balcolm Baldrige Method in the business world, and finds that this method cannot be applied to all MSMEs. However, it is possible for an MSMEs that have a vision and mission to enter the stock market, then the 7 pillars of Malcolm Baldrige's assessment can be pioneered which pillars can be developed as early as possible.